Strengthening School Education through Block Resource Centres and Cluster Resource Centres An Assessment - Singh, Pooja; Kurian, Tintu (JOURNAL OF INDIAN EDUCATION, 2018)
Sarva Shiksha Abhiyan is a centrally sponsored programme of the Ministry of Human Resource Development (MHRD), Government of India for ensuring quality education in schools. It has widened the scope of school reform efforts by ensuring improved participation from parents and the community. It also envisages bridging of gender and social gaps. Since ensuring quality was the main target under SSA, many interventions were made so as to make the school system more effective. One among these interventions was the establishment of Cluster Resource Centres (CRCs) and Block Resource Centres (BRCs). These academic support structures were visualised as the structures for ensuring quality in schools by providing necessary academic inputs and coordinating community mobilisation activities on a regular basis. This paper discusses the role, objectives and status of BRCs and CRCs across various States and UTs in the country. The paper also tries to explore how useful are BRCs and CRCs in delivering their academic inputs for the betterment of elementary education in India. The National Council of Educational Research and Training (NCERT) with the support of the MHRD has launched a programme for the implementation of Quality Monitoring Tools (QMTs) across various States and UTs in the country. Responses received from various States and UTs have been used as secondary data for the study.